Methicillin-resistant Staphylococcus aureus (MRSA) infection in hospitalized patients is dominated by community-acquired strains: genomic epidemiological evidence - Jingxia Dang; Yuhui Geng; Ting Pan; Ping Zhang; Mingbo Chen; Dongfeng Pan; Peifeng Liang (PLoS ONE, 2026)
Objective This study aimed to systematically investigate the molecular epidemiological characteristics of methicillin-resistant Staphylococcus aureus (MRSA) in Ningxia hospitals, to elucidate their genetic evolutionary relationships, and to delineate the genomic and phenotypic profiles of the dominant lineages. Methods Clinical isolates of MRSA strains collected between 01/01/2024 and 30/06/2024 were analyzed, employing second-generation gene sequencing technology, combined with MLST and SCC mec typing, along with evaluation of drug resistance and virulence genes. A phylogenetic tree was constructed to analyze strain homology. Results A total of 74 non-duplicate Staphylococcus aureus strains (67 MRSA and 7 MSSA) were collected. The most common clonal strain was ST59-IVa, accounting for 46.27%. This strain exhibited a high prevalence of resistance genes mecA and blaZ , at 91.04%. All five ST22-IVa strains were found to lack mecA and erm genes but showed β-lactam resistance, while possessing both lukS/F-PV ( PVL ) and tsst-1 virulence genes, indicating a significant toxicity risk. Genetic evolution analysis revealed that ST3355, ST4513, and ST59 were closely related, all belonging to SCC mec types IVa; the other ST types exhibited mutations at various loci, with ST5 as the central node, resulting in a wider array of ST and SCC mec typing. Conclusion The ST59-IVa clone is the predominant MRSA strain in Ningxia hospitals, exhibiting multidrug resistance and virulence gene profiles consistent with national trends. However, the emergence of hypervirulent ST22-IVa strains with atypical resistance mechanisms warrants increased vigilance. We recommend enhancing the rational use of antibiotics in hospitals and implementing molecular surveillance for these highly virulent strains.